PRODUCTION, PURIFICATION AND FIBRINOLYTIC CHARACTERIZATION OF ALKALINE PROTEASE FROM EXTREMOPHILIC SOIL FUNGI - P. PALANIVEL; L. ASHOKKUMAR; R. BALAGURUNATHAN (International Journal of Pharma and Bio Sciences, 2013)
The fungal populations in the alkaline soil samples collected from Eastern Ghats, Kolli hills region was studied by using potato dextrose agar medium. The samples possessed an average of 15X104 colony forming unit per gram of soil. Among this population 23 strains of fungi belong to five genus such as Trichoderma, Aspergillus, Penicillium, Rhizopus and Mucor were isolated. Protease producing fungal species was screened by Casein and Skimmed milk agar. Among the isolates three strains of Aspergillus spp., one Mucor sp. and one strain of Curvularia sp. showed greater proteolytic activity in both of the medium. An isolate of Aspergillus strain KH 17 showed maximum zone of proteolysis in screening media and greater enzyme activity in submerged fermentation 215U/ml in complex media containing casein. The effect of physiochemical parameters studied includes different carbon, nitrogen sources, pH and temperature. Among the parameters tested 1 % starch, 3% soya bean meal, pH 9 and temperature of 25 to 300C showed greater induction in enzyme production. The crude enzyme of cell free extract was concentrated by ammonium sulphate and dialysis. The precipitate showed 4.1 fold greater activities and dialyzed precipitate showed 6.7 fold greater specific activity per milligram protein than the crude. The fibrinolytic activity of the partially purified enzyme was determined, it showed prompt fibrinolytic activity. The area of clearance by alkaline protease was observed to be 64.5 ± 2.4 mm2. From this study it is found that the alkaline protease isolated from Aspergillus strain KH 17 has a great scope of medicinal, diagnostic and industrial applications.